Searching protein 3-D structures for optimal structure alignment using intelligent algorithms and data structures - Novosád, Tomáš; Snášel, Václav; Abraham, Ajith; Yang, Jack Y (IEEE transactions on information technology in biomedicine, 2010)
In this paper, we present a novel algorithm for measuring protein similarity based on their 3-D structure (protein tertiary structure). The algorithm used a suffix tree for discovering common parts of main chains of all proteins appearing in the current research collaboratory for structural bioinformatics protein data bank (PDB). By identifying these common parts, we build a vector model and use some classical information retrieval (IR) algorithms based on the vector model to measure the similarity between proteins--all to all protein similarity. For the calculation of protein similarity, we use term frequency × inverse document frequency ( tf × idf ) term weighing schema and cosine similarity measure. The goal of this paper is to introduce new protein similarity metric based on suffix trees and IR methods. Whole current PDB database was used to demonstrate very good time complexity of the algorithm as well as high precision. We have chosen the structural classification of proteins (SCOP) database for verification of the precision of our algorithm because it is maintained primarily by humans. The next success of this paper would be the ability to determine SCOP categories of proteins not included in the latest version of the SCOP database (v. 1.75) with nearly 100% precision.
Keywords: Protein Structure, Tertiary; Reproducibility of Results; algoritmy; Algorithms; reprodukovatelnost výsledků; výpočetní biologie; proteiny; strukturní homologie proteinů; data mining; Artificial Intelligence; databáze proteinů; Humans; Databases, Protein; Structural Homology, Protein; umělá inteligence; Data Mining; Computational Biology; Proteins; terciární struktura proteinů; lidé